2010
DOI: 10.1177/1096348010382236
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Reward Program Membership and Commitment on Hotel Loyalty

Abstract: This research evaluated the role of reward membership and commitment on switching costs, defined as the price at which consumers would switch to a nonpreferred hotel brand. Online survey respondents were classified by reward tier and two types of commitment: value (reward program benefits) and affective (emotional attachment to brand). The results showed that all reward program members exhibit value commitment but upper tier members are more likely to develop an emotional bond. Participants rated likelihood to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(125 citation statements)
references
References 30 publications
9
115
0
1
Order By: Relevance
“…The finding of this study was also consistent with previous studies (Dagger et al, 2011;Tanford et al, 2010;Adidam et al, 2004;Park and Him, 2003) that relationship benefits characterized as superior quality of services relative to other suppliers have a positive influence on relationship commitment. The construct of relationship benefits is a significant determinant of relationship commitment; PTE providers may consider enhance their benefits provided to students in order to increase students' commitment to schools.…”
Section: Discussionsupporting
confidence: 92%
“…The finding of this study was also consistent with previous studies (Dagger et al, 2011;Tanford et al, 2010;Adidam et al, 2004;Park and Him, 2003) that relationship benefits characterized as superior quality of services relative to other suppliers have a positive influence on relationship commitment. The construct of relationship benefits is a significant determinant of relationship commitment; PTE providers may consider enhance their benefits provided to students in order to increase students' commitment to schools.…”
Section: Discussionsupporting
confidence: 92%
“…In hospitality research, there have been a number of studies investigating loyalty program and guest loyalty (Mattila, 2006;Tanford, 2013;Tanford et al, 2011;Xie and Chen, 2014). The effectiveness of these loyalty programs in relation with creating customer loyalty has been studied.…”
Section: Customer Loyaltymentioning
confidence: 97%
“…For example, Xie and Chen (2014) found that psychological value of hotel loyalty programs has a significant impact on active loyalty. In addition, Tanford et al (2011) discovered differential effects of loyalty programs on guests' switching intentions. They found that low reward tier members or those with high value commitment were more price sensitive.…”
Section: Customer Loyaltymentioning
confidence: 97%
“…Loyalty programs play important roles in customer retention in many industries, including hotel chains, airlines, retail stores, and fi nancial institutions (Berezan, Raab, Tanford & Kim 2013;Han & Ryu 2009;Meyer-Waarden 2008;Tanford, Raab & Kim 2010). The perceived value that the customers attached to their experience with loyalty program such as what the program provides or does for members is reffered to as program benefi ts (Holbrook & Hirschman 1982;Kim, Lee, Choi, Wu & Johnson 2013;Mimouni-Chaabane & Volle 2010).…”
Section: Literature Review Loyalty Program Benefitsmentioning
confidence: 99%